(untitled) (Indonesian Sports Justice Review, 2024)
Sports sponsorship plays a pivotal role in the financing of professional sports in Indonesia, but the practice raises important questions about economic justice and fairness. This paper examines the economic justice of sports sponsorship, with a focus on how sponsorship deals impact the equitable distribution of resources within the sports industry. It assesses the power dynamics between sponsors, sports organizations, and athletes, analyzing how large sponsorship deals often concentrate resources in elite sports while sidelining grassroots programs and less popular sports. The research explores the ethical considerations surrounding sponsorship, including issues of monopolization, exploitation of athletes, and the commercial pressures placed on sports federations. The paper argues for a more balanced approach to sponsorship, proposing models that ensure fairer financial distribution across all levels of sport and safeguard the interests of athletes and local communities.